2015
DOI: 10.1016/j.nmd.2015.06.460
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion body myositis with granuloma formation in muscle tissue

Abstract: Inclusion body myositis is a form of inflammatory myopathy. We identified 4 cases of inclusion body myositis showing granuloma formation in muscle tissue and aimed to assess the features of this atypical form of the inclusion body myositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…In most cases we saw myofiber atrophy with subsequent invasion of connective and adipose tissue. The results are in accordance with observations made by others [12,17,27,36,37]. In a few cases hypertrophic myofibers in IBM patients were also reported [12,27].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In most cases we saw myofiber atrophy with subsequent invasion of connective and adipose tissue. The results are in accordance with observations made by others [12,17,27,36,37]. In a few cases hypertrophic myofibers in IBM patients were also reported [12,27].…”
Section: Discussionsupporting
confidence: 93%
“…In our study the clinical features, including weakness of upper and lower extremities, difficulty in climbing stairs as well as patients' ages were typical and similar to other reports [12,27,34]. Moreover, similarly to Hermanns et al [4] and Sakai et al [17] we observed periodical increases in the levels of CK and LDH enzymes in the studied patients' serum. In patients from a study conducted in China the average value of CK was 397.38 IU/L, whereas for LDH it was 218.21 IU/L [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations